An Analysis of Internal Factors Affecting the Study Continuation Interest of High School Students in Banda Aceh Toward Universitas Syiah Kuala - Mulyani, Riska (Syiah Kuala University, 2025)
Interest is a psychological tendency that drives individuals to choose certain objects or activities based on their needs, later manifested through attention and active engagement. In high school students (SMA), interest in pursuing higher education typically begins to form in the 11th grade as awareness of future planning increases. However, a phenomenon observed in several high schools in Aceh, particularly in Banda Aceh, shows that many high-achieving students prefer to continue their studies outside the province, despite the presence of a well-accredited university Universitas Syiah Kuala (USK) which offers 67 study programs across 12 faculties and serves around 30,000 students. This study aims to verify this trend using a quantitative survey approach conducted among public high school students in Banda Aceh. The main focus is to identify the best model representing student interest data and to reveal factors influencing their decision to choose USK. Using logistic regression due to the binary categorical nature of the dependent variable (interested vs. not interested), the study found that at a 10% significance level, three variables significantly influence students interest: affiliation ability (X), goal orientation (X), and hope for the future (X). Among these, goal orientation (X) had the strongest influence, with an odds ratio of 1.712. This indicates that the stronger a students academic or career goals, the higher their tendency to choose Universitas Syiah Kuala for further education.